[Hypothetical examples demonstrating the effect of excise taxes] (Tufts Archival Research Center, 2007)
Missing Page(s); Hypothetical example proving that a selective excise tax alters the decisions of consumers "by changing the price of the taxed product in relation to the prices of the untaxed goods and services." Demonstrates that a selective excise tax reduces consumer satisfaction and lead to a loss of "consumer surplus."